Synovial sarcoma--a misnomer. - Miettinen, M. (1984)
For an evaluation of the putative histogenetic relationship of synovia and synovial sarcomas, normal synovia, villonodular synovitis, and synovial sarcomas were compared for their patterns of expression of intermediate filaments of keratin and vimentin type and epithelial membrane antigen and for lectin binding sites. The lining cells in both normal synovia and villonodular synovitis reacted with anti-vimentin antibodies, but not with antibodies to different types of keratins or epithelial membrane antigen. The cleft-lining cells in synovial sarcoma, on the other hand, showed only keratin positivity, and epithelial membrane antigen could also be detected in these cells. Nonneoplastic synovial lining cells bound peanut agglutinin (PNA), Ricinus communis agglutinin (RCA), soybean agglutinin (SBA), concanavalin A (Con A), and wheat germ agglutinin (WGA) conjugates, but not Ulex europaeus I lectin (UEA I). In contrast, the epithelial-like cleft lining cells in synovial sarcomas showed an apical cytoplasmic binding of PNA, UEA I, RCA, and SBA, and binding of WGA to the whole cytoplasm but did not bind Con A. The distinct differences between synovial lining cells and synovial sarcoma cells speak against synovial cell features in synovial sarcoma. These results indicate that synovial sarcoma is a carcinosarcomalike tumor with true epithelial differentiation, and the term "synovial sarcoma" apparently is a misnomer that should be abandoned.